Matrix-Mediated Delivery of Silver Nanoparticles for Prevention of Staphylococcus aureus and Pseudomonas aeruginosa Biofilm Formation in Chronic Rhinosinusitis - Bhuvanesh Yathavan; Tanya Chhibber; Douglas Steinhauff; Abigail Pulsipher; Jeremiah A. Alt; Hamidreza Ghandehari; Paris Jafari (MDPI AG, 2023)
Chronic rhinosinusitis (CRS) is a chronic health condition affecting the sinonasal cavity. CRS-associated mucosal inflammation leads to sinonasal epithelial cell death and epithelial cell barrier disruption, which may result in recurrent bacterial infections and biofilm formation. For patients who fail medical management and elect endoscopic sinus surgery for disease control, bacterial biofilm formation is particularly detrimental, as it reduces the efficacy of surgical intervention. Effective treatments that prevent biofilm formation in post-operative patients in CRS are currently limited. To address this unmet need, we report the controlled release of silver nanoparticles (AgNps) with silk-elastinlike protein-based polymers (SELPs) to prevent bacterial biofilm formation in CRS. This polymeric network is liquid at room temperature and forms a hydrogel at body temperature, and is hence, capable of conforming to the sinonasal cavity upon administration. SELP hydrogels demonstrated sustained AgNp and silver ion release for the studied period of three days, potent in vitro antibacterial activity against Pseudomonas aeruginosa (**** p < 0.0001) and Staphylococcus aureus (**** p < 0.0001), two of the most commonly virulent bacterial strains observed in patients with post-operative CRS, and high cytocompatibility with human nasal epithelial cells. Antibacterial controlled release platform shows promise for treating patients suffering from prolonged sinonasal cavity infections due to biofilms.